2011
DOI: 10.3177/jnsv.57.9
|View full text |Cite
|
Sign up to set email alerts
|

Relieving Occupational Fatigue by Consumption of a Beverage Containing γ-Amino Butyric Acid

Abstract: SummaryTo elucidate the effect of ␥ -aminobutyric acid (GABA) on both psychological and physical fatigue and on the performance advances for task solving, we assigned an arithmetic task for the Uchida-Kraepelin Psychodiagnostic Test (UKT) to 30 healthy Japanese subjects, 9 of whom were diagnosed as having chronic fatigue. The subjects were administered 250 mL of a test beverage containing GABA at the dose of 0, 25, and 50 mg before assigning task for the UKT. Psychological fatigue assessed by the Visual Analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Moreover, at least five different studies have reported that the oral administration of GABA or GABA-supplemented food/beverages (corresponding GABA amounts of about 50–100 mg) has had positive effects on human health. These effects include: (i) the reduction of psychological stress in people who performed arithmetic tasks (Nakamura et al, 2009; Kanehira et al, 2011; Yoto et al, 2012); (ii) the reduction of stress in acrophobic subjects exposed to heights (Abdou et al, 2006); (iii) an increased ability to perform prioritized planned actions (Steenbergen et al, 2015). …”
Section: Glu/gaba: Receptors Signaling and Transportmentioning
confidence: 99%
“…Moreover, at least five different studies have reported that the oral administration of GABA or GABA-supplemented food/beverages (corresponding GABA amounts of about 50–100 mg) has had positive effects on human health. These effects include: (i) the reduction of psychological stress in people who performed arithmetic tasks (Nakamura et al, 2009; Kanehira et al, 2011; Yoto et al, 2012); (ii) the reduction of stress in acrophobic subjects exposed to heights (Abdou et al, 2006); (iii) an increased ability to perform prioritized planned actions (Steenbergen et al, 2015). …”
Section: Glu/gaba: Receptors Signaling and Transportmentioning
confidence: 99%
“…Kanehira et al . demonstrated an anti-fatigue effect from GABA ingestion on salivary secretion levels of chromogranin A (CgA) and cortisol following an arithmetic task used as a fatigue load [9]. Nakamura et al .…”
Section: Introductionmentioning
confidence: 99%
“…The chromogranin A (CgA) and salivary cortisol are known stress markers in humans [108], CgA being ubiquitously secreted in several tissue types, including, as recently discovered, in the submandibular glands [109], [110]. Kanehira et al (2011) observed that salivary secretion levels of chromogranin A were significantly lower in subjects who did intake 25 and / or 50 mg of GABA in comparison with the control group [111]. Other studies also report the GABA effect on relaxation and stress reduction.…”
Section: Gabamentioning
confidence: 78%
“…Other studies also report the GABA effect on relaxation and stress reduction. Abdou et al (2006) found that oral administration of GABA increased significantly alpha waves and decreased beta waves in the brain, and has maintained the levels of immunoglobulin A in saliva, when the subjects were subjected to stress conditions, such as crossing a suspension bridge [112]. This study showed that GABA could induce relaxation by decreasing anxiety while increasing immunity under stress conditions.…”
Section: Gabamentioning
confidence: 81%